Seasonal Evaluation of Antigenic Bacterial Infections Among Working Class in the Inner City of Houston - Ebere C. Anyanwu; Mohammed Morad; Andrew W. Campbell (The Scientific World Journal)
This paper evaluates the monthly, quarterly, and seasonal variation of antigenic bacterial infections among the working class in the inner city of Houston using the Wellcogen Rapid Test methods. One of the aims was to demonstrate how this method could be used effectively in screening patients at risk and preventing the spread of antigenic bacteria such as Streptococcus pneumoniae, Haemophilus influenzae b, Streptococcus (Strep b), and Neisseria meningitidis (mainly group c and b). A total of 2,837 patients were screened for bacterial infections; 908 (32%) were male and 1,929 (68%) were female. The age range was between 2 and 70 years. Of the total group, 356 (12.5%) patients were positive; 203 (57%) were female while 153 (43%) were male (male/female ratio of 1:1.3). Medically underserved and immune suppressed populations are the most affected by these bacterial infections. Blacks are the most affected (48%) compared to Native Americans (1%), but children under 10 years of age have the highest incidence. This research showed, in addition, that the Wellcogen Rapid Tests are effective (356 cases identified) for a rapid screening of infectious bacteria. Explanation for these results was probably due to poor living conditions, poor hygiene, and viral immune suppression in adults and immature immune systems in neonates and children under 10 years of age.